Customizing oxygen–containing functional groups for reduced graphene oxide film supercapacitor with high volumetric performance. (1st August 2022) - Zhao, Xin; Zhou, You; Xu, Yali; Huang, Cong; Shen, Yuping; Zhang, Yan; Fan, Zefu; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: The electrochemical performance of graphene films is greatly restricted, which is mainly ascribed from low content of electrochemically active oxygen–containing functional groups (AOFGs). Herein, a customized strategy is proposed to increase the ratio of AOFG in reduced graphene oxide film for improving the electrochemical performance. In detail, the highly oxidative graphene oxide (GO) precursor is initially prepared by adjusting the oxidation time, which facilitates the transformation of inert oxygen–containing functional groups (IOFGs) like COC to AOFGs CO. Subsequently, a moderate thermal treatment process is applied for the reduction of graphene oxide films, which achieves the enhancement of electrical conductivity without removing too many AOFG. As a result, the reduced oxygen–enriched graphene oxide film (rOGF) exhibits a high gravimetric capacitance of 549.6 F g −1 at 2 A g −1 with a high density of 1.5 g cm −3, corresponding to an ultrahigh volumetric capacitance of 824.4 F cm −3 . The exceptional rate performance (506.9 F cm −3 at 20 A g −1 ) in the three–electrode system is also achieved. In addition, the assembled symmetrical supercapacitor delivers a high energy density of 55.2 Wh L −1 or 36.8 Wh kg −1 and highly power density of 1350 W L −1 or 900 W kg −1 in the aqueous electrolyte. Highlights: The ORGO film is prepared by optimizing the oxidation time and C=O is provided more conducive to improving the capacitance performance The rOGF graphene oxide film delivers a high volumetric capacitance of 824.4 F cm −3 at the packing density of 1.5 g cm −3 . A superior capacitance retention of 137.5% after 10 000 cycles at 10 A g −1 is realized in a two-electrode system.